Kesulitan Kebebasan Berpendapat Kelompok LGBT di Indonesia Menurut Teori Utilitarianisme Jeremy Bentham - Khadafi Wijaya Wijaya (Triwikrama: Jurnal Ilmu Sosial, 2023)
Freedom of opinion is something that should be free in our social environment in order to implement aspects of human rights. There are no exceptions on the subject of Human Rights, just that in reality not everyone who fights for freedom of opinion gets what they desire. Freedom of opinion does not always mean freedom, there are environmental aspects when freedom of opinion is upheld, as in the case with LGBT groups in Indonesia. Indonesia itself has a majority Muslim population, which rejects the existence of LGBT. With a majority vote, Jeremy Bentham's theory of utilitarianism can be applied in order to calculate pain and pleasure to gain benefits from the phenomenon of LGBT voices.